ANALISIS PERAN KEPALA SEKOLAH DAN STAKEHOLDER DALAM PENGUATAN PENDIDIKAN KARAKTER DI SD N0. 11 PEDUNGAN - Ida Bagus Gede Surya Abadi; Chindytia Chindytia; Dharia Rizkyla Ramadhani; Anak Agung Istri Mas Wiryani; Ni Putu Oktavia Kusuma Sari (STKIP Pesisir Selatan, 2026)
This study was conducted due to the suboptimal implementation of character education strengthening in elementary schools caused by limited coordination between school principals and stakeholders. The study aimed to analyze the roles of the principal and stakeholders in strengthening character education at SD No. 11 Pedungan. The study employed a descriptive qualitative approach, and the data were collected through observation, interviews, and documentation. The findings showed that the principal had a strategic role in planning, implementing, supervising, and evaluating character education programs through various habituation activities. Stakeholders, including teachers, parents, school committees, and the community, also contributed to supporting the implementation of the programs. Although several obstacles were identified, such as limited resources, student discipline issues, and less effective communication, the character education programs produced positive impacts on students’ behavior. Therefore, collaboration between the principal and stakeholders was considered an important factor in the successful strengthening of character education in elementary schools.